The association between effectiveness of first-line treatment and second-line treatment in gastro-oesophageal cancer. (October 2021) - van Velzen, Merel J.M.; Pape, Marieke; Dijksterhuis, Willemieke P.M.; Slingerland, Marije; van Voorthuizen, Theo; Beerepoot, Laurens V.; Creemers, Geert-Jan; Derks, Sarah; Mohammad, Nadia H.; Verhoeven, Rob H.A.; van Laarhoven, Hanneke W.M.
Abstract: Background: Population-based predictive factors for the effectiveness of second-line palliative systemic therapy in gastro-oesophageal cancer are not available. This study investigates the predictive value of effectiveness of first-line treatment for second-line treatment outcomes in gastro-oesophageal cancer in a real-world setting. Methods: Patients with metastatic gastro-oesophageal cancer diagnosed in 2010–2017 who were treated with second-line therapy after disease progression on first-line therapy were identified from the Netherlands Cancer Registry. Patients were divided into four groups as per duration of time to treatment failure (TTF) of the first line (0–3, 3–6, 6–9 and >9 months), and the association with overall survival (OS) and second-line TTF was assessed using Kaplan-Meier curves and two-sided multivariable regression models. Results: Median OS since the start of the second line of patients (n = 611) with first-line TTF of 0–3, 3–6, 6–9 and >9 months was 4.0, 4.1, 5.5 and 7.1 months, respectively (P < 0.001). Median second-line TTF of patients with first-line TTF of 0–3, 3–6, 6–9 and >9 months was 2.8, 2.4, 3.0 and 4.5 months, respectively (P < 0.001). Patients with first-line TTF of >9 months showed a longer OS than patients with first-line TTF of 0–3 months (adjusted hazard ratio (HR) 1.90; 95% confidence interval (CI) 1.46–2.47), 3–6 months (adjusted HR 1.88; 95% CI 1.47–2.39) and 6–9 months (adjusted HR 1.31; 95% CI 1.04–1.65). Results for second-line TTF were similar. Conclusions: This study shows a positive correlation between effectiveness of first-line therapy and outcomes of second-line therapy in gastro-oesophageal cancer. Physicians should take duration of the first line into account when considering second-line palliative systemic therapy. Highlights: First-line time to treatment failure (TTF) is predictive for second-line TTF. First-line TTF is predictive for second-line overall survival. Clinicians should consider TTF when discussing the second line with patients.